PENGEMBANGAN KOLEKSI DALAM BIDANG PENGADAAN BAHAN PUSTAKA DI SEKOLAH TINGGI ILMU KESEHATAN SUMATERA UTARA (STIKESSU) MEDAN - Shinta Nofita Sari (Jurnal Pustaka Ilmiah, 2017)
This research hold in Sekolah Tinggi Ilmu Kesehatan Sumatera Utara (Stikessu) Medan, the aim of this research is to know how is the development collection in supplying the library stock in Stikessu. The method is descriptive research with qualitative approach. The informers is all the librarier of Stikessu. The technique of the data collections are interview, observation and library study. The result of this research shows that the development collection in supplying the library stock in Stikessu are though buying from the publisher directly, order from publisher, and from the gift or contribution from the users or university students who will graduate by giving money which is already decidedby the head of Stikessu. It will use to library needed or library progress.